Influence of whole-wheat consumption on fecal microbial community structure of obese diabetic mice - García Mazcorro, José Francisco; Ivanov, Ivan; Mills, David A.; Noratto, Giuliana D. (2016)
The digestive tract of mammals and other animals is colonized by trillions of metabolically active microorganisms. Changes in the gut microbiota have been associated with obesity in both humans and laboratory animals. Dietary modifications can often modulate the obese gut microbial ecosystem towards a more healthy state. This phenomenon should preferably be studied using dietary ingredients that are relevant to human nutrition. This study was designed to evaluate the influence of whole-wheat, a food ingredient with several beneficial properties, on gut microorganisms of obese diabetic mice. Diabetic (db/db) mice were fed standard (obese-control) or WW isocaloric diets (WW group) for eight weeks; non-obese mice were used as control (lean-control). High34 throughput sequencing using the MiSeq platform coupled with freely-available computational tools and quantitative real-time PCR were used to analyze fecal bacterial 16S rRNA gene sequences. SCFAs were measured in feces using HPLC-PDA. Results showed no statistical difference in final body weights between the obese-control and the WW group. Almost 9,000 different bacterial species (Operational Taxonomic Units at 97% similarity) were detected in all mice but the bacterial diversity (number of OTUs) did not differ among the treatment groups. The abundance of Ruminococcaceae, a family containing several butyrate-producing bacteria, was found to be higher in obese (median: 6.9%) and WW-supplemented mice (5.6%) compared to lean (2.7%, p = 0.02, Kruskal43 Wallis test). Fecal concentrations of butyrate were higher in obese (average: 2.91 mmol/mg of feces) but especially in WW-supplemented mice (4.27 mmol/mg) compared to lean controls (0.97 mmol/mg), while fecal succinic acid was lower in the WW group compared to obese but especially to the lean group. WW consumption was associated with ~3 times more relative abundance of Lactobacillus spp. compared to both obese and lean control mice. PCoA plots of weighted UniFrac distances revealed a distinctive clustering of lean microbial communities separately from both obese and WW-supplemented mice (p = 0.001, ANOSIM test). Predictive metagenome analysis using PICRUSt revealed significant differences in several metabolic features of the microbiota among the treatment groups, including fatty acid biosynthesis, carbohydrate and energy metabolism as well as synthesis and degradation of ketone bodies (p < 0.01). However, obese and WW groups tended to share more similar abundances of gene families compared to lean mice. Using an in vivo model of obesity and diabetes, this study suggests that daily WW supplementation for eight weeks may not be enough to influence body weight or to output a lean-like microbiome, both taxonomically and metabolically. However, WW58 supplementation was associated with several statistically significant differences in the gut microbiome compared to obese controls that deserve further investigation.